1966
DOI: 10.1063/1.1708145
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties and Color-Center Formation in Thin Films of Molybdenum Trioxide

Abstract: The optical absorption spectrum of thin films of MoO3 has been measured over the temperature range from 77° to 290°K. The fundamental absorption edge occurs at 3300 Å with an absorption coefficient of 105 cm−1. A stoichiometric film of MoO3 shows three absorption peaks at 3350, 2880, and 2700 Å, respectively, and these are suggested to be due either to exciton formation or to transitions involving a split valence band. Values for the refractive index have been measured in the wavelength range 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
135
1

Year Published

1970
1970
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(152 citation statements)
references
References 6 publications
16
135
1
Order By: Relevance
“…80,88,89 It has been previously demonstrated that oxygen vacancies, impurities and defects create additional states between the valence and conduction band resulting in a reduction of the optical band gap yielding typical fluorescence features centered around 400-450 nm (2.75-3.1 eV). 80,88,[90][91][92][93][94] Accordingly, it has been suggested that photoluminescence on MoOx (where x3) films provides a valuable handle to probe crystallinity, stochiometry and even surface roughness of the samples. 91 However, the broad near-band edge emission at < 400 nm usually obscures the lower energy features which are characteristic of sample quality.…”
Section: Photoluminescencementioning
confidence: 99%
“…80,88,89 It has been previously demonstrated that oxygen vacancies, impurities and defects create additional states between the valence and conduction band resulting in a reduction of the optical band gap yielding typical fluorescence features centered around 400-450 nm (2.75-3.1 eV). 80,88,[90][91][92][93][94] Accordingly, it has been suggested that photoluminescence on MoOx (where x3) films provides a valuable handle to probe crystallinity, stochiometry and even surface roughness of the samples. 91 However, the broad near-band edge emission at < 400 nm usually obscures the lower energy features which are characteristic of sample quality.…”
Section: Photoluminescencementioning
confidence: 99%
“…The foregoing result is explained in terms of charge carrier injection provided from ZnSe particles into the MoO 3 film through the barrier at the interface of both materials. Moreover, the decrease of the thermochromic response above certain annealing temperatures, e.g., 200 • C for the MoO 3 films, has been associated with the bleaching of MoO 3 due to the replenishment of oxygen vacancies when thermal annealings take place in air or O 2 atmospheres [1]. A further increase in the annealing temperature leads to crystallization of the MoO 3 films [2]; this process is connected with other changes in the material properties, such as the bandgap energy, as observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This material is being used in an increasingly wide variety of applications, ranging from photocatalytic processes and electrochemistry to dielectric coatings. In addition, considerable attention has been given to the chromogenic properties of MoO 3 , that is, the ability to change its optical properties due to the formation of color centers when exposed to specific external agents [1,2]. In particular, when coloration is induced by heat, it is named a thermochromic material.…”
Section: Introductionmentioning
confidence: 99%
“…The amorphous film has a perovskite-like type structure which consists of corner-sharing MoO 6 octahedra (Carcia & McCarron III 1987;Ramans et al 1987;Granqvist 1994) and has been produced by a number of techniques. The most common way of producing these films is by thermal evaporation from a resistive source (Deb & Chopoorian 1966;Deb 1968;Rabalais et al 1974;Yao et al 1990Yao et al , 1992Chudnovskii et al 1992). Vacuum evaporation is the standard technique; however, evaporation under slightly reactive conditions (Ramans et al 1987) and flash evaporation (Julien et al 1995) have also been used.…”
Section: (B) Photochromism Of Molybdenum Oxide Thin Filmmentioning
confidence: 99%